Logopēda un pirmsskolas pedagoga sadarbība skaņu izrunas traucējumu mazināšanā pirmsskolas vecuma bērniem - Spriņģe, Ilze (Latvijas Universitāte, 2020)
Darba autore: Ilze Spriņģe. Darba vadītāja: Prof., Dr. paed. Sarmīte Tūbele. Diplomdarba temats: logopēda un pirmsskolas pedagoga sadarbība skaņu izrunas traucējumu mazināšanā pirmsskolas vecuma bērniem. Darba mērķis: noskaidrot logopēda un pirmsskolas pedagoga sadarbības iespējas skaņu izrunas traucējumu mazināšanā pirmsskolas vecuma bērniem. Pētījuma jautājums: kādas ir logopēda un pirmsskolas pedagoga sadarbības iespējas skaņu izrunas traucējumu mazināšanā? Darbam ir trīs daļas. Pirmajā daļā apkopotas speciālistu atziņas par pirmsskolas bērnu attīstību veselumā un bērniem ar skaņu izrunas traucējumiem. Otrajā daļā, analizējot literatūru un normatīvos aktus, noskaidroti pirmsskolas pedagoga un logopēda galvenie uzdevumi un viņu sadarbības teorētiskais skaidrojums. Trešajā daļā analizēti pētījumā iegūtie dati par reālo situāciju pirmsskolas pedagogu un logopēdu sadarbībā, kā arī piedāvāts un aprakstīts minēto speciālistu sadarbības modelis pirmsskolas iestādē X. Modeļa ietvaros piedāvāti arī līdzekļi pedagoga darbam skaņu izrunas traucējuma koriģējoši attīstošajā darbībā. Darbā gūtās atziņas iekļautas secinājumos un ieteikumos. Diplomdarbs sastāv no 60 lapaspusēm, darba izstrādē izmantoti 58 literatūras avoti, darbā iekļauti 9 attēli, 7 tabulas un pievienoti 4 pielikumi.

Author : Ilze Spriņģe Head of work: Prof., Dr. paed.Sarmīte Tūbele Subject of the diploma: Cooperation between a speech therapist and a preschool teacher in reducing sound pronunciation disorders for preschool children. Aim of the papre: to investigate the possibilities of cooperation between a speech therapist and a preschool teacher in reducing sound pronunciation disorders for preschool children. Research question: what are the possibilities of cooperation between a speech therapist and a preschool teacher in reducing sound pronunciation disorders? The paper consists of three parts. The first part summarizes the findings of specialists about the development of preschool children as a whole and children with sound pronunciation disorders. In the second part, analyzing the literature and regulatory enactments, the main tasks of a pre-school teacher and a speech therapist and the theoretical explanation of their cooperation are clarified. The third part is dedicated to analyse of data obtained in the study on the real situation in the cooperation of pre-school teachers and speech therapists. The developed model of cooperation of the mentioned specialists in the pre-school institution X are also analysed in the third part. The model also offers tools for the pedagogue's work in the corrective development of sound pronunciation disorder. The findings of the work are included in the conclusions and recommendations. The paper consists of 60 pages; 58 literature sources were used in the development of the paper, the work includes 9 figures, 7 tables and 4 appendices. Keywords: preschool, speech therapist, teacher, cooperation, sound pronunciation disorders.
Collaboration of speech therapist and preschool educator in reduction of speech sound pronunciation disorders in preschool age children
Keywords: Pedagoģija; pirmsskola; logopēds; pedagogs; sadarbība; skaņu izrunas traucējumi